Brain volume, asymmetry and intellectual impairment in relation to sex in early-onset schizophrenia. - Collinson, S; Mackay, C; James, A; Quested, D; Phillips, T; Roberts, N; Crow, T (2003)
BACKGROUND: Accumulating evidence suggests that early-onset schizophrenia arises from a disturbance in the normal trajectory of cerebral development. AIMS: To investigate brain structure, asymmetry and IQ in early-onset schizophrenia. METHOD: Volumes of left and right cerebral hemispheres and IQ were assessed in 33 participants with early-onset DSM-IV schizophrenia and 30 members of a matched, normal control group. RESULTS: Total brain volume was significantly smaller in the group with early-onset disease ('cases') relative to the control group (4.5%), especially for the left hemisphere in males (6.0%). A significant sex x diagnosis interaction in hemisphere asymmetry revealed that the female cases group had significantly reduced rightward asymmetry relative to the female control group and that the male cases tended to have reduced leftward asymmetry relative to the male control group. Decreased left hemisphere volume in males and decreased rightward hemispheric asymmetry in females correlated with reduced IQ. CONCLUSIONS: Sexually dimorphic alterations in asymmetry correlate with degree of intellectual impairment in early-onset schizophrenia.